PEMBERANTASAN TERORISME BERORIENTASI HAM - Dwi Haryadi (Masalah-Masalah Hukum, 2014)
Eradicating terrorism has now become a national and global agenda that should be done to protect society. Densus 88 from Indonesian National Police, the executor of this effort, must not only stick to the principle of upholding the law and human rights, but also not be discriminatory. To optimize the preventive actions of human rights violation by this force, there is an understanding and implementation process of the code of conduct set out in the regulations, especially the principle and standards of human rights implementation in Indonesian National Police duty